2021
DOI: 10.1002/brb3.2295
|View full text |Cite|
|
Sign up to set email alerts
|

Modified Renshen Yangrong decoction enhances angiogenesis in ischemic stroke through promotion of MicroRNA‐210 expression by regulating the HIF/VEGF/Notch signaling pathway

Abstract: Objective: This study aims to investigate the efficacy of modified Ginseng Yangrong decoction (GSYRD) promoting angiogenesis after ischemic stroke. Methods:In an in vivo study, rats that survived surgery were allocated into four groups: the control group and model group were treated with normal saline, the GSYRD group was treated with 18.9 mg/kg of GSYRD daily, and the positive control group was treated with Tongxinluo (TXL) (1 g/kg/d). At the end of the seven-day treatment, the area of cerebral infarction, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…We have previously found that 86 exosomal tsRNA was down-regulated in the plasma of ONFH patients compared with the healthy individuals by small RNA sequencing ( Fang et al, 2020 ). To further investigate the molecular mechanism of exosomal tsRNA involved in angiogenesis of ONFH, we finally screened tsRNA-15797 and tsRNA-10520, according to the evidence that their target genes were involved in angiogenesis-related pathways, including HIF-1α signaling pathway ( Zhang et al, 2018 ), VEGF signaling pathway ( Liang et al, 2021 ), Wnt signaling pathway ( Jiang et al, 2015 ) and TGF-beta signaling pathway ( Wang et al, 2013 ) ( Figure S1 ). Subsequently, to further verify the expression of tsRNA-15797 and tsRNA-10520 in plasma exosomes from ONFH patients, we first isolated exosomes derived from plasma of ONFH patients and healthy subjects, and comprehensively characterized the morphologies and structures of exosomes by TEM and NTA methods.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously found that 86 exosomal tsRNA was down-regulated in the plasma of ONFH patients compared with the healthy individuals by small RNA sequencing ( Fang et al, 2020 ). To further investigate the molecular mechanism of exosomal tsRNA involved in angiogenesis of ONFH, we finally screened tsRNA-15797 and tsRNA-10520, according to the evidence that their target genes were involved in angiogenesis-related pathways, including HIF-1α signaling pathway ( Zhang et al, 2018 ), VEGF signaling pathway ( Liang et al, 2021 ), Wnt signaling pathway ( Jiang et al, 2015 ) and TGF-beta signaling pathway ( Wang et al, 2013 ) ( Figure S1 ). Subsequently, to further verify the expression of tsRNA-15797 and tsRNA-10520 in plasma exosomes from ONFH patients, we first isolated exosomes derived from plasma of ONFH patients and healthy subjects, and comprehensively characterized the morphologies and structures of exosomes by TEM and NTA methods.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the effects of RSYRD on MI, experimental mice were divided into four groups: the SHAM group, in which the mice with thoracotomy were intragastrically administered normal saline (NS); the SHAM + RSYRD group (SHAM + R), in which the mice with thoracotomy were intragastrically administered with RSYRD; the LAD ligated group (MI), in which the mice with LAD ligation were intragastrically administered NS; and the MI + RSYRD group (MI + R), in which the mice with LAD ligation were intragastrically administered with RSYRD. According to previous studies, RSYRD was intragastrically administered at a dose of 38 g/kg per day to the SHAM + R and MI + R groups for 3 days following surgery ( Liang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research have indicated that RSYRD can inhibit platelet activity in patients with ischemic heart disease and promote the proliferation, migration, and DNA synthesis of human umbilical vein endothelial cells ( Sheng et al, 2019 ). Remarkably, RSYRD has been shown to promote angiogenesis and cerebral protection following ischemic brain injury by activating the HIF/VEGF/NOTCH signaling pathway via miRNA-210 ( Liang et al, 2021 ). These findings suggest that RSYRD may have a protective role in MI.…”
Section: Introductionmentioning
confidence: 99%
“… 144 New researches show that GSYRD can activate HIF/VEGF/Notch signaling pathway through miR-210 to achieve enhanced angiogenesis after cerebral ischemia. 145 …”
Section: Angiogenesismentioning
confidence: 99%